2015
DOI: 10.1007/s11274-015-1814-5
|View full text |Cite
|
Sign up to set email alerts
|

Changing bacterial profile of Sundarbans, the world heritage mangrove: Impact of anthropogenic interventions

Abstract: Mangrove microbial communities and their associated activities have profound impact on biogeochemical cycles. Although microbial composition and structure are known to be influenced by biotic and abiotic factors in the mangrove sediments, finding direct correlations between them remains a challenge. In this study we have explored sediment bacterial diversity of the Sundarbans, a world heritage site using a culture-independent molecular approach. Bacterial diversity was analyzed from three different locations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 69 publications
2
13
0
Order By: Relevance
“…Pathogenic microorganisms are known to be important degraders of petroleum hydrocarbons. Several strains of infectious microbes such as Burkholderia 32 , Stenotrophomonas 33, 34 and Mycobacterium 35 have been shown to harbor impressive capabilities for degradation of a variety of petroleum hydrocarbons. In the present study, pathogens such as Mycobacterium and Burkholderia , were identified as genus level biomarkers for C samples and Tb samples respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic microorganisms are known to be important degraders of petroleum hydrocarbons. Several strains of infectious microbes such as Burkholderia 32 , Stenotrophomonas 33, 34 and Mycobacterium 35 have been shown to harbor impressive capabilities for degradation of a variety of petroleum hydrocarbons. In the present study, pathogens such as Mycobacterium and Burkholderia , were identified as genus level biomarkers for C samples and Tb samples respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the M samples, two component systems for starvation of phosphate (M00434), a limiting nutrient for mangroves 34 and metal tolerance (M00499) were detected as differentially abundant (Fig. 3, Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Biogeography (distinct soil depths and locations) may be a major determinant factor that influences bacterial structure. In addition, anthropogenic interference may contribute to this difference, because various degrees of human activities (urbanization, pollution, and aquaculture) have different effects on environmental competitiveness and co-shaping the microbial communities (Marcial et al, 2008; Basak et al, 2015; Chakraborty et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…S2, Supplementary Table S3). In the M samples, two component systems for starvation of phosphate (M00434), a limiting nutrient for mangroves 59 and metal tolerance (M00499) were detected as differentially abundant (Fig. 5, Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%